Experimental Investigation of Storage Tank Design on the Performance of a Solar Water Heating System: Review Approach - Ambalal Patil, Swapnil; Patel, D.M (International Journal of Computer Sciences and Engineering, 2022)
Solar energy is easily available in nature, pollute less, priceless and therefore it is accepted as one of the most capable unconventional energy sources. The effective use of solar energy is held up by the intermittent nature of its availability, limiting its use and success in domestic and industrial applications especially in water heating. This topic is about to investigation and optimization of solar water heating system by varying zig-zag tube arrangement with natural convection. By using zig-zag tube arrangement in the solar water heating system the efficiency will slightly increase. The aim of the research work is to improve the performance of solar water heater by changing the tubes geometry and material of tube. The purpose of this study is to improve the technology available for solar water heater. It is mature technology still it has many opportunities for modifications. Further research work is required in the field of cost and performance of collector plates and glazing cover plates.